Irritation, Hedonic, and Antioxidant Activity Testing of Sunkist Orange Peel (Citrus sinensis (L.) Osbeck) Peel-Off Gel Mask Formulation - Nofita, Nofita; Sofyan, Shefira; Saputra Yasir, Angga (Universitas Muhammadiyah Surakarta, 2024)
Sunkist orange peel is a rich source of antioxidants beneficial for skin protection, making it a promising ingredient in cosmetic products like peel-off gel masks. This study investigated the sensory profile, primary irritation index (PII), and antioxidant activity of peel-off gel mask formulations containing Sunkist orange peel extract (Citrus sinensis (L.) Osbeck). The extract was obtained through maceration using 96% ethanol, with a mean yield of 9.95 ± 1,2 %. Phytochemical analysis identified the presence of polyphenols, tannins, and flavonoids. The extract was incorporated into peel-off gel mask formulations and evaluated for quality parameters (organoleptic properties, pH, viscosity, and drying speed), sensory characteristics, PII, and antioxidant activity using the DPPH method. All formulations fulfilled the required quality standards. Sensory evaluation indicated that Formula III (FIII) was the most favored by respondents across all stages of application (before, during, and after use). The irritation index test on 25 volunteers revealed no irritation, with PII values ranging from 0 to 0.4, classifying the preparations as non-irritating. Antioxidant evaluation showed that the peel-off gel with 2% extract exhibited an IC-50 value of 23.38 ppm, categorizing it as a very strong antioxidant. These findings highlight the potential of Sunkist orange peel extract in peel-off gel masks, combining excellent antioxidant properties with favorable sensory and safety profiles. Further optimization may enhance its application in skincare products.